The Practice of Amal Masjid in Madura - Masyithah Mardhatillah; Muhammad Taufiq (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2020)
This paper aims to portray a practice called ‘amal masjid’ which is very popular at Madura. It is performed at the street to get donation for mosque(s) construction. However, local MUI (Majelis Ulama Indonesia; Indonesian Ulama Council) issued a legal regulation to forbid it. This condition comes to a problem because the practice is the real solution for funding source. On the other hand, its existence is problematic as it disturbs even endangers street users as well as the amal men. The primary data of this research is from observation and interview at two location of amal masjid in Pamekasan and Sumenep. This paper is going to answer three questions. First, to what extent does the amal masjid represent the identity of local Maduresse Moslems? Second, how do the Maduresse Muslim negotiate the amal masjid to the local government and other stakeholders? Third, how can the amal masjid be located as a distinctive local Muslim philanthropy and the blueprint on ideal philanthropy to the world?